Exploring Mosul Food Proverbs: A Cognitive Perspective - Muhammed Idrees Hasan (Zanco Journal of Human Sciences, 2025)
Metaphor stands out as one of the most well-known theories that deal with non-literal language. This concept is viewed by Lakoff and Johnson (1980a) as understanding abstract concepts through more tangible objects. This view differs from other theories that consider metaphor as merely as a play of words. This research investigates the utilization of food metaphors in Mosuli Arabic proverbs. Its aim is to shed light on the bases and motives of these metaphors; furthermore, it seeks how abstract ideas are conceptualized and comprehended through the use of terms related to food in Mosuli Arabic proverbs. It hypothesizes that food-related terms are employed to comprehend and interpret a diverse range of abstract concepts. Furthermore, it suggests that the bases of metaphor are culture and experience. Written and oral data are collected then analysed on two levels: the first level is concerned with getting the correct explanation and discourse scenarios where these proverbs might be used. The second level consists of two sub-levels. Two models are used on the first part to investigate implicit metaphors. The two models are taken from the works of Lakoff and Turner (1989) on "GENERIC IS SPECIFIC" and Lakoff and Johnson (2003) on "Metaphors We Live By." Thus, the two models are used to reveal the metaphorical meaning of food in Mosuli Arabic proverbs. The second part investigates explicit metaphors using the paradigm proposed by Lakoff and Johnson (2003). This research concludes that the conceptual metaphor theory is able to reveal a various number of abstract ideas that are comprehended in reference to more tangible objects. Additionally, the metaphorical conceptualization is motivated by experience and cultural values.